Economic viability of the piaucu Leporinus macrocephalus (Garavello & Britski, 1988) production - Takahashi, L. S.; Goncalves, F. D.; de Abreu, J. S.; Martins, MIEG; Ferreira, ACM (Universidade de São Paulo (USP), 2004)
Brazilian fish farms presented an accelerated development during the early 90's, mainly because of the increase in fee-fishing operations. To meet the demand of this market, fish production and supply became excessive and, as a consequence, the number of fee-fishing operations, farmers and the final selling price, decreased. This study analyzes the technical aspects, production cost, profitability and economic viability of the production of piaucu (L. macrocephalus) in ponds, based on information from a rural property. Feeding and fingerling costs amount to approximately 47.1 % of the total production cost, representing together with the final selling price the most important factor affecting profitability. The payback period was 8.3 years, the liquid present value US$ 291.07, the internal return margin 9%, and the income-outcome ratio was 1.01, which represents an unattractive investment as a projection based on current conditions. The improvement in productive efficiency enhances the economic valuation index, and that the relative magnitude of cost and income are the most important points for the economic viability of the studied farm.
Keywords: costs; profitability; economic analysis; sensitivity analyses; fish farming